Assesment of prevalence of Metabolic Syndrome in Patients on Atypical Antipsychotics: A Cross-Sectional Study in Erode (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Metabolic syndrome, characterized by central obesity, dyslipidemia, hypertension, and impaired glucose metabolism, increases the risk of cardiovascular disease and type 2 diabetes. Atypical antipsychotics are widely used in psychiatric disorders but are associated with adverse metabolic effects. Evidence from regional Indian populations remains limited. Objective: To estimate the prevalence of metabolic syndrome among patients receiving atypical antipsychotics and identify associated demographic, lifestyle, and clinical factors. Methods: A prospective cross-sectional study was conducted in Erode from January to June 2026 among 361 adults receiving atypical antipsychotics for at least six months. Metabolic syndrome was diagnosed using NCEP ATP III criteria. Demographic, clinical, medication, and lifestyle data were collected using structured forms and the WHO STEPS instrument. Clinical assessments included waist circumference, blood pressure, fasting glucose, triglycerides, and HDL cholesterol. Multivariate logistic regression identified independent predictors. Results: Metabolic syndrome was identified in 22.4% of participants. Increased waist circumference, elevated triglycerides, and reduced HDL cholesterol were the most common abnormalities. Olanzapine or clozapine use, treatment duration exceeding 12 months, sedentary lifestyle, and unhealthy dietary habits were significant independent predictors. Conclusion: Metabolic syndrome is prevalent among atypical antipsychotic users. Regular metabolic screening, lifestyle modification, and integrated psychiatric-metabolic care are essential to reduce long-term cardiometabolic complications.
Keywords: long-term cardiometabolic complications; HDL cholesterol; NCEP ATP III